(3GdCZPjI hGdCTQHI ddCUMGAs - (3eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s ((3eMeO Hf eMeO Hf eSYhO s)
(3ChdgG (B:s
(3bGd GdTjN GdaGVd eMeO Hf Ydi GdSeQbfOi Ef GdhGLH Ydi cd Pi dH Cf jJbQH Edi Gddg hjJhSd Edjg hCMSf GdhSGFd hCLhO GdPQGjY EeJKGd GdChGeQ hGdfhGgi s
(3BNQgG (B:s
(3aUd ai CSHGH GdEMSGS hGdESJaQGZ ,SHH GdEMSGS VYa GdOGaYI s
(3fSNI QGHYI ef GdbSe GdQGHY ef GdfLjHjGJ cGdSGHbIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
(3agQS GdWH (B- (3U (B195 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B271 s
Keywords: (3GdWHs